Epidermal growth factor regulation by autophagy‐mediated lncRNA H19 in murine intestinal tract after severe burn. Issue 10 (16th April 2020) - Li, Cuijie; Zhuang, Mengmeng; Zhu, Bo; Li, Ye; Zhang, Wenwen; Yan, Hao; Zhang, Pan; Li, Dan; Yang, Juan; Sun, Yuan; Chen, Haijun; Cui, Qingwei; et al.
Abstract: To investigate the regulation of epidermal growth factor (EGF) by autophagy‐mediated long non‐coding RNA (lncRNA) H19 in the intestinal tracts of severely burned mice. C57BL/6J mice received third‐degree burns to 30% of the total body surface area. Rapamycin and 3‐methyladenine (3‐MA) were used to activate and inhibit autophagy, and the changes in LC3 and Beclin1 levels were assessed by Western blotting. The effect of autophagy on lncRNA H19 was detected by qRT‐PCR. Adenovirus‐mediated overexpression of lncRNA H19 in IEC‐6 cells was used to assess the effects of lncRNA H19 on EGF and let‐7g via bioinformatics analysis, Western blotting and qRT‐PCR. let‐7g mimic/inhibitor was used to overexpress/inhibit let‐7g, and qRT‐PCR and Western blotting were used to detect the effects of let‐7g on EGF. The expression levels of LC3‐II, Beclin1 and lncRNA H19 were increased in intestinal tissues and IEC‐6 cells after rapamycin treatment but were reversed after 3‐MA treatment. LC3‐II, Beclin1 and lncRNA H19 levels increased in intestinal tissues after the burn, and these increases were more significant after rapamycin treatment but decreased after 3‐MA treatment. The lncRNA H19 overexpression in IEC‐6 cells resulted in increased and decreased expression levels of EGF and let‐7g, respectively. Furthermore, overexpression and inhibition of let‐7g resulted in decreased and increased expression of EGF, respectively. Taken together, intestinal autophagy is activated after a serious burn, which can increase the transcription level of lncRNA H19. lncRNA H19 may regulate the repair of EGF via let‐7g following intestinal mucosa injury after a burn.